2014
DOI: 10.1007/s11033-014-3572-0
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor of mud crab, Scylla serrata: molecular characterisation, ontogeny and functional expression analysis following ligand exposure, and bacterial and viral infections

Abstract: Toll-like receptors are sentinels of innate immune system, which recognise pathogen-associated molecular patterns, and subsequently activate production of antimicrobial peptides to contain the infection. In the present study, we cloned and characterised a Toll gene from Scylla serrata (SsToll) encoding 1005 amino acids with typical Toll-like receptor domain topology. Phylogenetic analysis revealed that it belongs to insect-type invertebrate Toll family showing 100 % identity with Scylla paramamosain (SpToll). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…For AMPs synthesised and contained within the granules of haemocytes, mature proteins would be released in a regulated way at times of need, with synthesis of new proteins induced by pattern recognition receptors, such as Toll or IMD. Certainly in recent years a growing number of sequence reports of Toll receptors from various decapod species have been published, showing that these genes are expressed across a wide range of tissues and are up-regulated after immune challenge (Arts et al, 2007;Yang et al, 2007Yang et al, , 2008Mekata et al, 2008;Vidya et al, 2014). A very recent study on crayfish has shown that Toll regulates expression of crustin, ALF and lysozyme in P. clarkii, and penaeidins in shrimp with attacin, metchnikowin, and drosomycin over-expressed in Drosophila S2 cells .…”
Section: Delivering the Goodsmentioning
confidence: 99%
“…For AMPs synthesised and contained within the granules of haemocytes, mature proteins would be released in a regulated way at times of need, with synthesis of new proteins induced by pattern recognition receptors, such as Toll or IMD. Certainly in recent years a growing number of sequence reports of Toll receptors from various decapod species have been published, showing that these genes are expressed across a wide range of tissues and are up-regulated after immune challenge (Arts et al, 2007;Yang et al, 2007Yang et al, , 2008Mekata et al, 2008;Vidya et al, 2014). A very recent study on crayfish has shown that Toll regulates expression of crustin, ALF and lysozyme in P. clarkii, and penaeidins in shrimp with attacin, metchnikowin, and drosomycin over-expressed in Drosophila S2 cells .…”
Section: Delivering the Goodsmentioning
confidence: 99%
“…Most of these reported PRRs are found to be expressed ubiquitously in all the tissues analysed. Immune challenge studies have indicated differential response of the PRRs to different infectious agents such as white spot syndrome virus (WSSV) and bacteria (Vidya et al 2014;Deepika et al 2014;Dechamma et al 2015;Sreedharan et al 2017Sreedharan et al , 2018Li et al 2019b;Deepika et al, 2020aDeepika et al, , 2020b.…”
Section: Pathogen Recognitionmentioning
confidence: 99%
“…Immune challenge studies have indicated differential response of the PRRs to different infectious agents such as white spot syndrome virus (WSSV) and bacteria (Vidya et al . 2014; Deepika et al . 2014; Dechamma et al .…”
Section: Pathogen Recognitionmentioning
confidence: 99%
“…For the experimental setup, the cell count was maintained at 2 × 10 6 cells/well. The hemocytes were then exposed to 10 μg/ml LPS or 10 μg/ml PGN (Sigma, USA) prepared in serum-free medium and incubated at 28 C. The concentration of ligands was selected based on a previous study by Vidya et al (2014). Subsequently, at 2, 6, 12, 24, 48, and 72 hr post-exposure, the hemocytes from two wells were harvested and pooled.…”
Section: In Vitro Ligand Stimulationmentioning
confidence: 99%